Implementation of Duties and Functions of the Regional Revenue Agency of Minahasa Regency - H. Tumbel, Goinpeace; Wawointana, Thelma; Inof Riisyie Rantung, Margareth (Indonesian Association for Public Administration (IAPA), 2024)
Maintenance of local users, always connected with adequate finance, in order to meet the needs of the development of the area for the well-being of the community. As for increasing the local income, by leveraging the local real income in this case the local tax collection. As for the purpose of this research to find out, analyze the function of the Regional Revenue Agency of Minahasa district in the process of tax collection of catering houses, with the aim of maximizing the original income of the district Minahase district as well as to analyze any obstacles in the implementation of the functions of the regional income agency in Minahsa district to maximize the local income in this case, the collection of food tax. This research method uses qualitative methods. The use of this research is as an input material against bapenda to maximize the local income as well as some information from the informants cause of low income due to the masses there are taxpayers who do not pay taxes even there are who avoid paying taxes, then the lack of ability to work in the District Revenue Body of Minahasa District.